2017
DOI: 10.3389/fnins.2017.00411
|View full text |Cite
|
Sign up to set email alerts
|

Attention, in and Out: Scalp-Level and Intracranial EEG Correlates of Interoception and Exteroception

Abstract: Interoception, the monitoring of visceral signals, is often presumed to engage attentional mechanisms specifically devoted to inner bodily sensing. In fact, most standardized interoceptive tasks require directing attention to internal signals. However, most studies in the field have failed to compare attentional modulations between internally- and externally-driven processes, thus probing blind to the specificity of the former. Here we address this issue through a multidimensional approach combining behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 99 publications
10
72
0
Order By: Relevance
“…Similar modulation of early SEP components (P50) has previously been shown along with shifts of spatial attention (Forschack et al, 2017;Schubert et al, 2008). Given that HEP amplitude has been found to be significantly higher during interoceptive compared to exteroceptive attention (García-Cordero et al, 2017;Petzschner et al, 2019;Villena-González et al, 2017), we propose that the modulations of HEP amplitude reflect attentional shifts between external stimuli (exteroception) and internal bodily states (interoception). In line with this view, it has been suggested that the sudden ''ignition'' of a spontaneous internal activity can block external sensory processing (Dehaene & Changeux, 2005).…”
supporting
confidence: 79%
“…Similar modulation of early SEP components (P50) has previously been shown along with shifts of spatial attention (Forschack et al, 2017;Schubert et al, 2008). Given that HEP amplitude has been found to be significantly higher during interoceptive compared to exteroceptive attention (García-Cordero et al, 2017;Petzschner et al, 2019;Villena-González et al, 2017), we propose that the modulations of HEP amplitude reflect attentional shifts between external stimuli (exteroception) and internal bodily states (interoception). In line with this view, it has been suggested that the sudden ''ignition'' of a spontaneous internal activity can block external sensory processing (Dehaene & Changeux, 2005).…”
supporting
confidence: 79%
“…Consistent with the characterisation of the HEP as a neural correlate of precision-weighted interoceptive prediction error, many studies have reported attentional modulation of the amplitude of the HEP -for example, during tasks involving attending to heartbeat sensations relative to external stimuli (García-Cordero et al, 2017;Montoya, Schandry, & Müller, 1993;Petzschner et al, 2019;Schandry et al, 1986;Villena-González et al, 2017;Yuan, Yan, Xu, Han, & Yan, 2007).…”
mentioning
confidence: 67%
“…As expected, given these previous inconsistencies, we found no differences between groups in any of them (see Supporting Information Data S1 and Supporting Information Table S1). More particularly, HEP modulations have been widely shown to be autonomously reliable as a robust index of general attention to body-inner sensations (Garcia-Cordero et al, 2017;Garcia-Cordero et al, 2016;Pollatos & Schandry, 2004;Yoris, Abrevaya, et al, 2018;Yoris, García, Traiber, Santamaría-García, Esteves, et al, 2017;Yoris, García, Traiber, Santamaría-García, Martorell, et al, 2017) as well as other processes associated with body-brain communication, such as body awareness (Muller et al, 2015), emotional experience (Couto, Aldofi, Velasquez, et al, 2015), motivation (Weitkunat, 1990), attention (Montoya, Schandry, & Muller, 1993), and pain perception (Shao, Shen, Wilder-Smith, & Li, 2011). More particularly, HEP modulations have been widely shown to be autonomously reliable as a robust index of general attention to body-inner sensations (Garcia-Cordero et al, 2017;Garcia-Cordero et al, 2016;Pollatos & Schandry, 2004;Yoris, Abrevaya, et al, 2018;Yoris, García, Traiber, Santamaría-García, Esteves, et al, 2017;Yoris, García, Traiber, Santamaría-García, Martorell, et al, 2017) as well as other processes associated with body-brain communication, such as body awareness (Muller et al, 2015), emotional experience (Couto, Aldofi, Velasquez, et al, 2015), motivation (Weitkunat, 1990), attention (Montoya, Schandry, & Muller, 1993), and pain perception (Shao, Shen, Wilder-Smith, & Li, 2011).…”
Section: Heartbeat-evoked Potential: Preprocessing and Analysismentioning
confidence: 99%
“…Thus, following previous studies (Muller et al, 2015;Schulz et al, 2015), we focused our main analysis on HEP modulations, which provide critical information about the temporal dynamics of interoception. More particularly, HEP modulations have been widely shown to be autonomously reliable as a robust index of general attention to body-inner sensations (Garcia-Cordero et al, 2017;Garcia-Cordero et al, 2016;Pollatos & Schandry, 2004;Yoris, Abrevaya, et al, 2018;Yoris, García, Traiber, Santamaría-García, Esteves, et al, 2017;Yoris, García, Traiber, Santamaría-García, Martorell, et al, 2017) as well as other processes associated with body-brain communication, such as body awareness (Muller et al, 2015), emotional experience (Couto, Aldofi, Velasquez, et al, 2015), motivation (Weitkunat, 1990), attention (Montoya, Schandry, & Muller, 1993), and pain perception (Shao, Shen, Wilder-Smith, & Li, 2011). These properties highlight the relevance of the HEP as a reliable and self-sufficient nonbehavioral subclinical measure to afford critical insights of the cortical monitoring of internal signals.…”
Section: Heartbeat-evoked Potential: Preprocessing and Analysismentioning
confidence: 99%
See 1 more Smart Citation